SCENARIO MODEL TO REDUCE TRAFFIC CONGESTION USING INTELLIGENT TRANSPORTATION SYSTEMS - Suryani, Erma; Hendrawan, Rully Agus; Syafa’at, Fizar; Az-Zahra, Alifia (MATTER: International Journal of Science and Technology, 2020)
This study aims to develop a scenario model to reduce traffic congestion using intelligent transportation systems (ITS). ITS is an application of advanced technology in the fields of electronics, computers, and telecommunications to make transportation infrastructure and facilities more informative, smooth, safe, and comfortable. It encompasses the latest wireless, electronic, simulation, and automatic technology. As a method to develop the scenario model, system dynamics (SD) is utilized considering that it can accommodate a system with complex non-linearity, faster and easier sensitivity analyses through the tests on the structure of the models. SD has been used at the macroscopic and microscopic levels of the trafﬁc ﬂow to explore the interaction of transportation and urban planning as well as to evaluate the effect of different transport policies. ITS can reduce traffic congestion through the placement of several surveillance cameras in some corners of the city and is equipped with sensors to detect the number of vehicles. This detection results can be used as an input in setting the time for traffic signal control to reduce the volume of vehicles by prioritizing solid lines to get the green light so that the flow of heavy traffic can run first. With this scenario, traffic congestion is projected to decrease to be in the range of 0.71 – 0.79 (below the maximum saturation level of 0.85) due to the decrease in vehicle volume as the impact of the implementation of ITS.